Inhibición sinérgica entre iones yoduro y polisacáridos de Opuntia ficus indica y Prosopis pallida en la corrosión del acero 1.25Cr-0.5Mo - Vergara Roldan, Patricia Judith (2023)
The synergistic effect between the mixture of iodide ions (KI) and Opuntia ficus indica polysaccharide (OFI) and the mixture of iodide ions with Prosopis pallida (PP) on the corrosion inhibition of 1.25Cr-0.5Mo steel in 1M HCl at temperatures of 25 °C, 45 °C and 65 °C was studied and evaluated. The sample was obtained from a seamless 1.25Cr-0.5Mo steel pipe and electrochemical frequency modulation, electrochemical impedance spectroscopy, potentiodynamic polarization and polarization resistance techniques were used for the determination of inhibition efficiency. The highest inhibition efficiency between OFI + KI taking into account the four methods was obtained with 1 g.L −1 OF and 5 mM KI at 65 °C being 94% and between PP + KI was 94.7 % with 0.15 g.L −1 PP and 5 Mm KI at 65 °C. For both mixtures it was observed that the inhibition efficiency increased with temperature and KI dosage. It was noted that both mixtures conform to the Lagmuir isotherm and that with increasing temperature the energy oscillates between -30 and -40 kJ/mol demonstrating the spontaneity of the adsorbed film formation, furthermore it was observed that the free energy and enthalpy values show that the mixtures are chemically adsorbed. Likewise, the potentiodynamic polarization technique determined that the mixtures behave as mixed inhibitors with a preponderance in the inhibition of the anodic process.